Barriers and enablers to utilisation of the WHO surgical safety checklist at the university teaching hospital in Lusaka, Zambia: a qualitative study - Judith Munthali; Chiara Pittalis; Leon Bijlmakers; John Kachimba; Mweene Cheelo; Ruairi Brugha; Jakub Gajewski (BMC, 2022)
Abstract Background Surgical perioperative deaths and major complications are important contributors to preventable morbidity, globally and in sub-Saharan Africa. The surgical safety checklist (SSC) was developed by WHO to reduce surgical deaths and complications, by utilising a team approach and a series of steps to ensure the safe transit of a patient through the surgical operation. This study explored barriers and enablers to the utilisation of the Checklist at the University Teaching Hospital (UTH) in Lusaka, Zambia. Methods A qualitative case study was conducted involving members of surgical teams (doctors, anaesthesia providers, nurses and support staff) from the UTH surgical departments. Purposive sampling was used and 16 in-depth interviews were conducted between December 2018 and March 2019. Data were transcribed, organised and analysed using thematic analysis. Results Analysis revealed variability in implementation of the SSC by surgical teams, which stemmed from lack of senior surgeon ownership of the initiative, when the SSC was introduced at UTH 5 years earlier. Low utilisation was also linked to factors such as: negative attitudes towards it, the hierarchical structure of surgical teams, lack of support for the SSC among senior surgeons and poor teamwork. Further determinants included: lack of training opportunities, lack of leadership and erratic availability of resources. Interviewees proposed the following strategies for improving SSC utilisation: periodic training, refresher courses, monitoring of use, local adaptation, mobilising the support of senior surgeons and improvement in functionality of the surgical teams. Conclusion The SSC has the potential to benefit patients; however, its utilisation at the UTH has been patchy, at best. Its full benefits will only be achieved if senior surgeons are committed and managers allocate resources to its implementation. The study points more broadly to the factors that influence or obstruct the introduction and effective implementation of new quality of care initiatives.